Preparation and Characterization of Repaglinide Loaded Ethosomal Gel for the Treatment of NIDDM - Rathore, Anubha Rajawat (International Journal of Pharmaceutical & Biological Archive, 2013)
Preparation and Characterization of Repaglinide Loaded Ethosomal Gel for the Treatment of NIDDM